OPTIMALISASI STRATEGI PEMASARAN INDUSTRI KERUPUK PAK MUNCUL DI DESA PUNGGUL SIDOARJO GUNA MENINGKATKAN OMSET PENJUALAN - Salwa Sabrina Latif (CURVE: Journal of Economic, Business and Accounting, 2025)
This study aims to identify the internal and external factors of Pak Muncul's cracker industry based on a SWOT analysis in improving sales turnover and to determine the appropriate marketing strategies as a form of optimization to increase turnover in Pak Muncul's cracker industry. This study uses a qualitative approach with a case study type of research. A case study is an in-depth qualitative research approach used to investigate various groups of individuals, institutions, and so on over a certain period of time. The number of informants in this study was 12 people. This study uses in-depth interview methods, field observations, and data triangulation with SWOT analysis techniques. The results of this study indicate that Pak Muncul's cracker industry is in quadrant I. Quadrant I is a favorable position because it has both strengths and opportunities. The industry can take advantage of existing opportunities and adopt a strength-opportunity strategy by developing the company based on aggressive growth policies. The approach that should be applied in this position is a Growth Oriented Strategy. Expanding market reach, utilizing technology, and innovating products can be steps to further optimize the existing marketing strategy.